In silico Studies Combining QSAR Models, DFT-based Reactivity Descriptors and Docking Simulations of Phthalimide Congeners with Hypolipidemic Activity - Camila da Câmara Lopes; Maria Angélica Bonfim Oliveira; Regiane de Cássia M. U. de Araújo; Boaz Galdino de Oliveira (Orbital: The Electronic Journal of Chemistry, 2021)
In this current study, a selected group of physicochemical descriptors extracted from the formalism of the density functional theory were used for modeling a series of phthalimide congeners with tested hypolipidemic activity once. Based on unsupervised pattern recognition of HCA and PCA followed by the PLS regressions, the final content may be considered trustful for predicting the biological activity due to the results of r2cal = 0.937, r2CV = 0.591 and r2test = 0.85. Moreover, the molecular modeling was performed through the docking protocol for predicting the ligand pose on the HMG-CoA reductase. The protocols of the AutoDock Tools and AutoDock Vina were used for determining the interaction scores (ΔG) and inhibition constants (Ki). Among all congeners studied, the docking results pointed out a potential compound. By taking into account the widely known top selling drugs, and just as is well-known that atorvastatin is one of them due its capability to lower the cholesterol levels, the structure of this drug was subjected to a docking study in order to guide us to a better understanding of the results available here.DOI: http://dx.doi.org/10.17807/orbital.v13i3.1493